Tufts president John A. DiBiaggio at Michigan State University commencement - Unknown (Tufts Archival Research Center, 2005)
9x11, photographic print. Photograph from 1985 commencement ceremony at Michigan State University (MSU). From left to right: John A. DiBiaggio, Edgar L. Harden, John A. Hannah, Clifton R. Wharton, Jr. and M. Cecil Mackey. They were all presidents of MSU.